THE EXPERIENCE OF GOD AS REVELATION AND KNOWLEDGE OF THE TRIUNE GOD IN THE WORKS OF DIONYSIUS AREOPAGITE AND THEIR USE IN THE THEOLOGY OF DUMITRU STĂNILOAE - ARTEMI, Eirini (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2019)
Dumitru Staniloae, in his Dogmatic Theology develops the connection of the Experience of God as Revelation and knowledge of the Triune God based and on the works of Dionysius Areopagite. The divine essence remains inaccessible eternally. For this reason, the man as finite logic being should articulate a moderate thought. The knowledge of God commensurate with the ability of the finite man to know the infinite God. He doesn’t completely escape from the reality of darkness - a general characteristic of the created nature. The very fact that man was created out of nothing, and the characteristics of createdness and decay contain in his nature, this is an essential differentiation between him and his Creator. Thus, the basis for every human expression or knowledge about God is the fact for the ontological distinction between the created and the uncreated nature. The knowledge of God should be understood as the knowledge of God’s attributes and His modes of being, the direction from the heaven to the earth and not the opposite one. The sole ground of man’s knowledge of God is thus God’s self-revelation; it is premised on the idea of divine incomprehensibility. The term revelation signifies two things; that the knowledge of God itself by itself is impossible. However, God can be known (economically) through revelation, and a human being is capable of receiving this knowledge according to her/his capacity.